(untitled) (Semiárida, 2018)
In the course of evolution, plants have developed different responses and adaptations allowing them to survive under water deficit. These adaptation strategies can occur at physiological, cellular and molecular levels. At the latter one, gene expression codification would produce different proteins whose function may be: a) acting as protective molecules which contribute to water deficit tolerance, or b) acting as carriers of regulatory signals. Knowledge of these proteins and their functions can be used by Molecular Biology and Genetic Engineering to obtain plants tolerant to water limitations, as an important aid to agricultural production in regions with low hydric availability.